Providing first evidence of the behaviour and potential environmental impacts of an accidental underwater release of propane. (1st May 2021) - Bravo-Linares, Claudio; Araya, Claudio; Muñoz-Arcos, Enrique; Cabrera, Daniela; Bastidas, Natalia; Carrasco, Daniela; Córdova, Claudio; Mudge, Stephen M.
Abstract: Aquaculture activities in southern Chile demand floating devices to produce electricity powered by diesel generators. It has been recently proposed to replace this fuel with propane. However, little is known about the behaviour and possible environmental impacts of an accidental release of propane underwater. In this study we evaluated the impact of water temperature and salinity on the saturation and further release of propane under controlled laboratory experiments. Results showed that under extreme environmentally relevant scenarios (high and low temperature and salinity), propane saturated the water more quickly. However, while it is important to consider that saturation times can be similar (∼2 h), the magnitudes of propane dissolved can be different. Experiments showed that cold waters (5 °C) propane is dissolved twice than warm waters (20 °C). Residence time was more affected by water temperature and almost independent of water salinity. Propane may take at least 2 days to be released from waters (around 90% of the initial amount dissolved under laboratory conditions). Additionally, we evaluated the impact on dissolved oxygen displacement and the embryotoxicity of the dissolved fraction by using Zebrafish Embryo Toxicity Assay. Results showed that dissolved oxygen was quickly removed. However, the levels of dissolved oxygen were promptly recovered in the studied systems. We also observed that propane can generate genotoxic effects (3–10% mortality), but after 2 days the system can be almost free of propane and the effects may become much lower. Comparatively with the literature, propane showed to be less toxic than diesel and it is a viable and less environmentally hazardous replacement for diesel. Graphical abstract: Image 1 Highlights: Propane is a replacement diesel for fueling floating devices for aquaculture in Chile. Behaviour and toxicity of propane in water is shown. After two days propane in water may be completely removed. Toxicty as propane migrates to the surface decreased over time. Propane is a viable, less environmentally hazardous replacement for diesel. Abstract : Experimental finding reveals that propane is a viable, less environmentally hazardous replacement for diesel.